Estudo do comportamento térmico na cidade de Quixadá com base nas Zonas Climáticas Locais (LCZ) - Sousa Filho, Mario Rodrigues Pinto de (2023)
The emergence of a city causes intense transformation of the natural landscape, and, as the construction element advances over the space, it impacts its morphology and atmosphere. The urbanization produces different landscapes and climate realities in a city, with temperature and humidity different from those in natural environments. This will result in the emergence of urban climate (with a variety of microclimates) and, to study this, it is necessary to understand the landscape, as its different scales are the result of the interation between geo ecology (natural set) and geo urbanism (city morphology and function) in the city. With the advance growth of urban environments, a greater attention has been needed on urban climate (also in semiarid cities in the northeastern), in understanding its genesis, its effects on the population and formation of heat islands, for instance. The city of Quixadá goes through this process of growth over time, it has the largest population of the Sertão Central region and its elements present different microclimates, for this reason, the importance of studying its urban climate and investigating the existence of heat islands. Thus, throughout the chapters will be observed the thermal behavior of the air in the city of Quixadá through the classification method named Local Climate Zones (LCZ). There was an approach on how GIS (Geographical Information System) is a crucial tool in climatology, the importance of understanding the landscape in the design of LCZ, the generation of the climate zones and conduct of mobile transects for temperature measurement of the air. As for the analysis of urban climate of Quixadá, there was the combination between the creation of LCZ and the air temperature registration through mobile transects (to validate the climate zones) in the rainy and dry seasons. Through this combination, it was analyzed the thermal field of the city, shown by LCZ technics file, figures, maps and charts, whose result was the identification of heat islands in the urban environment. At last, there are presented the main results and suggested some measures to reduce the temperature of the city, bringing greater thermal comfort for the population.